# If $\alpha ,\beta $ are the roots of the equation ${x^2} + px - q = 0$ and $\gamma ,\delta $ are the roots of the equation ${x^2} + px + r = 0$, then the value of $(\alpha - \gamma )(\alpha - \delta )$ is

$

A)p + r \\

B)p - r \\

C)q - r \\

D)q + r \\

$

Answer

Verified

360.9k+ views

Hint: Here to solve this problem we get the given value we need to know the sum of the roots and products of roots of given quadratic equations. They have mentioned the roots of given equations.

Complete step-by-step answer:

We know that if there is any quadratic equation in the form $a{x^2} + bx + c = 0$.Then we know that

Sum of roots $ = -\dfrac{{{\text{ coefficient of x}}}}{{{\text{coefficient of }}{{\text{x}}^2}}}$

Product of roots $ = \dfrac{{{\text{constant term}}}}{{{\text{coefficient of }}{{\text{x}}^2}}}$

Here given equation is ${x^2} + px - q = 0$ whose roots are $\alpha ,\beta $

Now by using the above concept

Sum of the roots $\left( {\alpha + \beta } \right)$ $ = \dfrac{{ - p}}{1} = - p$

Product of roots $\left( {\alpha .\beta } \right) = \dfrac{{ - q}}{1} = - q$

Here it is also mentioned $\gamma ,\delta $ are the root of equation ${x^2} + px + r = 0$.

Sum of the roots $\left( {\gamma + \delta } \right) = \dfrac{{ - p}}{1} = - p$

Product of roots $\left( {\gamma \delta } \right) = \dfrac{r}{1} = r$

Now here we have to find the value of $(\alpha - \gamma )(\alpha - \delta )$

$ \Rightarrow \left( {\alpha - \gamma } \right)\left( {\alpha - \delta } \right)$

$ \Rightarrow {\alpha ^2} - \alpha (\gamma + \delta ) + \gamma \delta $

Since we the value $\gamma + \delta = - p$ and $\gamma \delta = r$.So now on substituting the value and further simplification we get

$ \Rightarrow q + r$

Option D is the correct one .

Note: In this problem before finding the value of given term we have got the required value of to solve the given term. So get the value we have used the sum of roots and products of roots of the given two functions. Here we have to concentrate on finding the sum of roots of the equation and product roots of the equation by using the formulas.

Complete step-by-step answer:

We know that if there is any quadratic equation in the form $a{x^2} + bx + c = 0$.Then we know that

Sum of roots $ = -\dfrac{{{\text{ coefficient of x}}}}{{{\text{coefficient of }}{{\text{x}}^2}}}$

Product of roots $ = \dfrac{{{\text{constant term}}}}{{{\text{coefficient of }}{{\text{x}}^2}}}$

Here given equation is ${x^2} + px - q = 0$ whose roots are $\alpha ,\beta $

Now by using the above concept

Sum of the roots $\left( {\alpha + \beta } \right)$ $ = \dfrac{{ - p}}{1} = - p$

Product of roots $\left( {\alpha .\beta } \right) = \dfrac{{ - q}}{1} = - q$

Here it is also mentioned $\gamma ,\delta $ are the root of equation ${x^2} + px + r = 0$.

Sum of the roots $\left( {\gamma + \delta } \right) = \dfrac{{ - p}}{1} = - p$

Product of roots $\left( {\gamma \delta } \right) = \dfrac{r}{1} = r$

Now here we have to find the value of $(\alpha - \gamma )(\alpha - \delta )$

$ \Rightarrow \left( {\alpha - \gamma } \right)\left( {\alpha - \delta } \right)$

$ \Rightarrow {\alpha ^2} - \alpha (\gamma + \delta ) + \gamma \delta $

Since we the value $\gamma + \delta = - p$ and $\gamma \delta = r$.So now on substituting the value and further simplification we get

$ \Rightarrow q + r$

Option D is the correct one .

Note: In this problem before finding the value of given term we have got the required value of to solve the given term. So get the value we have used the sum of roots and products of roots of the given two functions. Here we have to concentrate on finding the sum of roots of the equation and product roots of the equation by using the formulas.

Last updated date: 26th Sep 2023

â€¢

Total views: 360.9k

â€¢

Views today: 3.60k

Recently Updated Pages

What do you mean by public facilities

Slogan on Noise Pollution

Paragraph on Friendship

Disadvantages of Advertising

Prepare a Pocket Guide on First Aid for your School

What is the Full Form of ILO, UNICEF and UNESCO

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

The equation xxx + 2 is satisfied when x is equal to class 10 maths CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Drive an expression for the electric field due to an class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

What is the past tense of read class 10 english CBSE